EFFECT OF TEMPE POWDER FORTIFICATION ON CATFISH MEATBALL (clarias gariepinus) ON CONSUMER ACCEPTANCE - Aditya U Pardosi; Suardi Loekman; Desmelati ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was intended to determine the effect of tempe powder fortification on catfish meatball (Clarias gariepinus) on consumer acceptance in different amount of concentration. The used method was experimental. Which using Complete Random Design (CRD). The used treatment of tempe powder fortification (T) are in four level which T0 (0 g), T1 (25 g), T2 (50 g), T3 (75 g), from substance of producing weight with two times repetition. The results shows that the most likes treatment by panelis depend on organoleptic parameter is T0 treatment with The characteristic criteria is clean, shines and undull color, specific fish aroma, specific catfish flavor, compact and elastic texture. Whereas the best results depend on chemichal value T3 treatment is water amount (26,70%), protein value (60,24%), fat value (2,27%), and hard fiber (1,79%).Keywords: catfish, tempe powder, meatball.